Institutional change through development assistance: The comparative advantages of political and adaptive approaches - Michael Roll (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Development assistance often fails to achieve institutional change because of a limited consideration of the political nature of these reforms and the local context. In response, political and adaptive development assistance (PADA) approaches, such as 'Thinking and Working Politically' (TWP) and 'Problem-Driven Iterative Adaptation' (PDIA), have been developed in recent years. Politicians, practitioners and researchers increasingly want to know if these approaches are more effective than mainstream approaches to development assistance. To answer this question, this paper develops a framework by asking three more specific questions about the 'which', the 'where' and the 'what'. First, for which types of development problems is political and adaptive development assistance likely to work betterthan mainstream approaches? Second, where or in which contexts might this be the case? And third, what contributions can be expected from these approaches including, but going beyond, effectiveness? Available evidence is used to answer these questions. This paper finds that political and adaptive approaches have comparative advantages over mainstreamapproaches when either the problem is complex, the context is hard to predict, or the solution is contentious. The overall conclusion is that development policy needs a broader variety of approaches from which to choose based on which fits the problem and the context best.
Keywords: 320